2009
DOI: 10.3748/wjg.15.4695
|View full text |Cite
|
Sign up to set email alerts
|

Clonality and allelotype analyses of focal nodular hyperplasia compared with hepatocellular adenoma and carcinoma

Abstract: FNH, as a whole, is polyclonal, but some of the NAH lesions derived from it are already neoplastic and harbor similar allelic imbalances as HCAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…21 Typically, a so-called second hit is required to convert from polyclonal to monoclonal expansion and tumor formation. 22,23 No loss of heterozygosity in adrenal gland hyperplasia caused by an SDHB mutation is consistent with this process. Given our current finding, it seems that the MEN-2 syndrome and the SDH mutations predispose the adrenal medulla, and perhaps other organs containing chromaffin tissue, to abnormal accelerated growth that can eventually lead to monoclonal expansion of a subpopulation of mutated tumor cells and cause the formation of pheochromocytomas and paragangliomas.…”
mentioning
confidence: 56%
“…21 Typically, a so-called second hit is required to convert from polyclonal to monoclonal expansion and tumor formation. 22,23 No loss of heterozygosity in adrenal gland hyperplasia caused by an SDHB mutation is consistent with this process. Given our current finding, it seems that the MEN-2 syndrome and the SDH mutations predispose the adrenal medulla, and perhaps other organs containing chromaffin tissue, to abnormal accelerated growth that can eventually lead to monoclonal expansion of a subpopulation of mutated tumor cells and cause the formation of pheochromocytomas and paragangliomas.…”
mentioning
confidence: 56%
“…21,22,24 However, several small but recent pathological series found parts of the FNH nodules were monoclonal, suggesting, at least, partial neoplastic transformation. 25,26 These intriguing findings raise further questions about malignant potential but may be specific only for certain subtypes of FNH. In this regard, Bioulac-Sage et al, in a series that compares 13 telangiectatic FNH (tFNH) with 28 classical FNH and 17 hepatic adenomas, showed that 100% of tFNH are monoclonal in origin and more closely resemble hepatic adenomas than classical FNH.…”
Section: Histopathology and Pathogenesismentioning
confidence: 93%
“…It is a neoplasm of demonstrated clonal origin [20, 21] and has a small but nonnegligible risk of malignant transformation [22]. Hemorrhage, pain, and rupture are other, more frequent complications of HCA, and their likelihood is proportional to the size of the tumor [1].…”
Section: Hepatocellular Adenoma (Hca)mentioning
confidence: 99%